RANCANG BANGUN INDIKATOR PERGANTIAN PART BERKALA PADA SEPEDA MOTOR - Wagino Wagino; Wawan Purwanto; Dori Yuvenda; Muhammad Rifqi (Ensiklopedia of Journal, 2022)
The development research method can simply be defined as a research method that is intentional, systematic, aimed/directed to find, formulate, improve, develop, produce, test the effectiveness of products, models, methods/strategies/means, services.This research will start from August 2021 – September 2021 at the Automotive Engineering Workshop, Faculty of Engineering, Padang State University.Based on the results of the research that the author has done, it can be obtained that this research has produced a valid and effective periodic part replacement indicator tool for motorbike vehicles by applying a microcontroller, RTC, and SD card Module and SD Card as data storage for motorbike mileage so that it is known the age of the part from the results of the mileage measurement. So this tool is valid and functions as planned by previous researchers, and the tool is effective because it doesn't affect other systems, both mechanical and electrical. This tool has a power supply or current source from the battery, so the tool requires to be turned on and off manually.Keywords: Design; Part Change Indicator; Motorcycle